Color quality consideration when switching from FL to LED - Listowski, Maciej; Supronowicz, Robert (Photonics Letters of Poland, 2022)
Fluorescent lamps (FLs) used for general lighting due to European Union legislation will be withdrawn from sale by 2023. The LEDs which are proposed as substitute of FL should provide the same quality of lighting and visual comfort. The research on substituting FL lamps is based on the multi-criteria parameterization. It is indicates that LEDs substituting the FLs may not meet the end user expectations due to the Color Preference Criteria. The paper compare typical FL (4100 K) lamp named by CIE as illuminant FL3.5 with its corresponding LED substitutes available on the market. The LED substitute selection criterion were value of Corelated Color Temperature (CCT) and chromaticity point which was must be within ellipse provided by ANSI C78.376 document for 4100 K CCT. Full Text: PDF References W. Żagan, Conditions necessary to replacing the conventional lamps by energy-saving lamps, Przeglad Elektrotechniczny, R. 85, 100 (2009). DirectLink M. Zalesinska, J. Zablocka, K. Wandachowicz, "Measurement and evaluation of selected parameters for non-directional household lamps", Prz. Elektrotech. 94, 188 (2018). CrossRef D. Czyżewski, "LED substitutes of conventional incandescent lamps", Prz. Elektrotech. 88, 123 (2012). DirectLink D. Czyżewski, "LED substitutes of conventional incandescent lamps(2)", Prz. Elektrotech. 91, 199 (2015). CrossRef Document of the International Commission on Illumination CIE 015:2018 "Colorimetry, 4th Edition". CrossRef CIE 13.3-1995: Method of measuring and specifying colour rendering properties of light sources," Commission Internationale de l’Eclairage, Vienna, Austria (1995). DirectLink Y. Ohno, M. Fein, C. Miller, "Vision Experiment on Chroma Saturation 2016 DOE SSL R&D Workshop 14 for Color Quality Preference", CIE 216 :2015, 60 (2015). DirectLink Y. Ohno, "Practical Use and Calculation of CCT and Duv", LEUKOS- J. Illum. Eng. Soc. N. Am. 10, 47, (2014). CrossRef Y. Wang, M. Wei, "Preference among light sources with different Duv but similar colour rendition: a pilot study", Ligh. Res. Technol. 50, 1013 (2018). CrossRef M. Royer, Analysis of color rendition specification criteria, Light-Emitting Devices, Materials, and Applications. 10940. International Society for Optics and Photonics, (2019). CrossRef ANSI/IES TM-30-20, IES Method for Evaluating Light Source Color Rendition. DirectLink J. Kowalska, "Analysis of parameters describing the quality of the color rendering of light sources according to the IES TM-30-15 and the CIE 013.3-1995", Prz. Elektrotech. 93, 50 (2017). CrossRef J. Kowalska, I.Fryc, "Colour rendition quality of typical fluorescent lamps determined by CIE Colour Fidelity Index and Colour Rendering Index", Prz. Elektrotech. 95, 94 (2019). CrossRef D. Aurelien, et al., "Development of the IES method for evaluating the color rendition of light sources", Opt. Express, 23, 15888 (2015). CrossRef W. Żagan, "Honestly and prudently about LED - Future and present state of LED application in lighting", Prz. Elektrotech. 84, 1 (2008). DirectLink W. Żagan, "Theoretical considerations on luminous efficacy and colour rendering of light sources", Prz. Elektrotech. 89, 284, (2013). DirectLink M. Listowski, "The real and modeled values of photometric and colorimetric parameters comparison of white LEDs operating at wide temperature range", Prz. Elektrotech. 98, 57 (2022). CrossRef R. Supronowicz, J. Fan, M. Listowski, A. Watras, I. Fryc, "Application of different metrics for describing light color quality of white LED". Photonics Lett. Pol. 13, 31 (2021). CrossRef I.Fryc, "Measurement techniques of optical LEDs properties performed with compliance conformity with CIE 127:2007 standard", Prz. Elektrotech. 85, 317 (2009). DirectLink I. Fryc, T. Dimitrova-Grekow, "An Automated System for Evaluation of the Quality of Light Sources" Proceedings of 2016 IEEE Lighting Conference of the Visegrad Countries (Lumen V4), CrossRef P. Jakubowski, J. Kowalska, R. Supronowicz, I. Fryc, "The Influence of Spectral Measurements Uncertainty of Fluorescent Lamps on Calculated Value of Their Relative Melanopic Weighted Irradiance and Colour Quality Parameters", 2018 VII. Lighting Conference of the Visegrad Countries (Lumen V4), 1 (2018). CrossRef P. Zhu, H. Zhu, G. C. Adhikari, S. Thapa, "Design of circadian white light-emitting diodes with tunable color temperature and nearly perfect color rendition", OSA Contin. 2, 2413 (2019). CrossRef Q. Dai, Y. Huang, L. Hao, Y. Lin, K. Chen, "Spatial and spectral illumination design for energy-efficient circadian lighting", Build. Environ. 146, 216 (2018). CrossRef A. Sánchez-Cano, J. Aporta, "Optimization of Lighting Projects Including Photopic and Circadian Criteria: A Simplified Action Protocol". Appl. Sci. 10, 8068 (2020). CrossRef CIE International Standard DIS 026/E:2018 CIE System for Metrology of Optical Radiation for ipRGC-Influenced Responses to Light, CrossRef I. Fryc, P. Jakubowski, K. Kołacz, "Analysis of optical radiation parameters of compact discharge HID lamps and LED COB modules used for illuminating shop windows, Prz. Elektrotech. 93, 186 (2017). CrossRef I. Fryc, "LED’s spectral power distribution under different condition of operating temperature and driving current", Prz. Elektrotech. 86, 187 (2010). DirectLink D. Mozyrska, M. Wyrwas, I.Fryc, "The determination of the LEDs colorimetric parameters, in the range of their operating temperature", Prz. Elektrotech. 88, 232 (2012). DirectLink M. Kreissl, T. Q. Tien, J. W. Tomm, "Spatially resolved and temperature dependent thermal tuning rates of high-power diode laser arrays", Appl. Phys. Lett. 88, 133510 (2006). CrossRef K. Wandachowicz, K. Domke, "Measurements of the temperature-dependent changes of the photometrical and electrical parameters of LEDs", Prz. Elektrotech. 84, 114 (2008). DirectLink I. Fryc, "The spectral power distribution of LED driven by square shape pulses", Prz. Elektrotech. 88, 131 (2012). DirectLink J. Fan, Y. Li, I. Fryc, C. Qian, X. Fan, G. Zhang, "Machine-learning assisted prediction of spectral power distribution for full-spectrum white light-emitting diode". IEEE Photonics J. 12, 1 (2019). CrossRef R. Supronowicz, I. Fryc, "The LED spectral power distribution modelled by different functions - how spectral matching quality affected computed LED color parameters", Proceedings of Balkan Light Junior 2019 conference (ss. 1-4), (2019). CrossRef A. Kokka, et al., "Development of white LED illuminants for colorimetry and recommendation of white LED reference spectrum for photometry", Metrologia 55, 526 (2018). CrossRef ANSI C78.376-2014 Electric Lamps - Specifications For The Chromaticity Of Fluorescent Lamps. DirectLink